1998
DOI: 10.1002/mrm.1910390407
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous intracellular and extracelular pH measurement in the heart by 19F NMR of 6‐fluoropyridoxol

Abstract: 6-Fluoropyridoxol (6-FPOL) was evaluated as a simultaneous indicator of intracellular and extracellular pH and, hence, pH gradient in perfused rat hearts. After infusion, 19F NMR spectra rapidly showed two well-resolved peaks assigned to the intracellular and extracellular compartments, and pH was calculated on the basis of chemical shift with respect to a sodium trifluoroacetate standard. To demonstrate use of this molecule, dynamic changes in myocardial pH were assessed with a time resolution of 2 min during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 38 publications
0
39
0
Order By: Relevance
“…Aromatic reporter molecules tend to have a much larger chemical shift pH response. Analogs of vitamin B6, for example, 6-FPOL are highly sensitive to pH [11,279,[290][291][292]. We showed that 6-FPOL itself readily enters cells and provides well-resolved resonances reporting both intra-and extracellular pH (pHi and pHe), simultaneously, in whole blood (Fig.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 97%
See 2 more Smart Citations
“…Aromatic reporter molecules tend to have a much larger chemical shift pH response. Analogs of vitamin B6, for example, 6-FPOL are highly sensitive to pH [11,279,[290][291][292]. We showed that 6-FPOL itself readily enters cells and provides well-resolved resonances reporting both intra-and extracellular pH (pHi and pHe), simultaneously, in whole blood (Fig.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 97%
“…We showed that 6-FPOL itself readily enters cells and provides well-resolved resonances reporting both intra-and extracellular pH (pHi and pHe), simultaneously, in whole blood (Fig. 9) [279] and the perfused rat heart [290]. Ease of entry into blood cells may be related to facilitated transport, since vitamin B6 is naturally stored, transported, and redistributed by erythrocytes [293].…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
See 1 more Smart Citation
“…hydroxy-6-methyl-3,4-pyridinedimethanol) are highly sensitive to pH [45,[93][94][95]. Synthesis of 6-FPOL is Deutsch et al [86,87] championed the use of…”
Section: Fluoro Amino Acidsmentioning
confidence: 99%
“…6-FPOL accelerated and fell into the intermediate exchange regime readily enters cells and provides well resolved resonances causing severe line broadening. Based on this approach a reporting both intra-and extracellular pH (pHi and pHe), series of fluorinated agents was developed, particularly, simultaneously, in whole blood [45] and the perfused rat using mono-, di-and tri-D, L,-2-amino-3,3-difluoro-2-heart, as confirmed by 31 P NMR and pH electrodes [93]. In methyl propanoic acid (Table 4).…”
mentioning
confidence: 99%